(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: Neonatal death is responsible for about 45% of the total deaths of children under 5 years of age in Bangladesh. Among the leading causes of neonatal death are infections 36% (sepsis/pneumonia, tetanus and diarrhoea), pre-term birth (28%) and birth asphyxia (23%) which indicates the poor foetal outcome of complicated pregnancy and unhygienic birth process. Objective: To find out the foetal outcome of complicated pregnancy and to minimize foetal death. Methods: An observational study was done purposively on 107 recently delivered women in the Obstetrics and Gynecology Department of Dhaka Medical College Hospital from January 2011 to June 2011. Data were collected by face-to-face interviews of the respondents with a semistructured questionnaire. Verbal consents were taken prior to the interview. Results: Among the newborn baby 93.2% born alive and 6.8% were dead. The association between antenatal complication and birth weight was significant (p<0.05). The women with complicated pregnancies, about 45.2% delivered newborns of low birth weight. Antenatal complications showed a highly significant association with gestational age (p<0.05). About 38.4% of preterm babies born in such women have pregnancy complications. Antenatal complication had significant (p<0.05) association with birth asphyxia. The outcome of pregnancy was also significantly associated with antenatal complications (p<0.05). Conclusion: Almost every pregnancy is at risk. Regular ANC, early detection of complications, early referral and safe delivery can minimize adverse outcomes of pregnancy. JAFMC Bangladesh, Vol 20, No 1 (June) 2024:18-21